Sequential Observations of Flux Transfer Events, Poleward‐Moving Auroral Forms, and Polar Cap Patches. Issue 6 (13th June 2020) - Hwang, K.‐J.; Nishimura, Y.; Coster, A. J.; Gillies, R. G.; Fear, R. C.; Fuselier, S. A.; Petrinec, S. M.; Burch, J. L.; Dokgo, K.; Sibeck, D. G.; Giles, B. L.; Russell, C. T.; et al.
Abstract: We report the observation of solar wind‐magnetosphere‐ionosphere interactions using a series of flux transfer events (FTEs) observed by Magnetospheric MultiScale (MMS) mission located near the dayside magnetopause on 18 December 2017. The FTEs were observed to propagate duskward and either southward or slightly northward, as predicted under duskward and southward interplanetary magnetic field (IMF). The Cooling model also predicted a significant dawnward propagation of northward‐moving FTEs. Near the MMS footprint, a series of poleward‐moving auroral forms (PMAFs) occurred almost simultaneously with those FTEs. They propagated poleward and westward, consistent with the modeled FTE propagation. The intervals between FTEs, relatively consistent with those between PMAFs, strongly suggest a one‐to‐one correspondence between the dayside transients and ionospheric responses. The FTEs embedded in continuous reconnection observed by MMS and corresponding PMAFs individually occurred during persistent auroral activity recorded by an all‐sky imager strongly indicate that those FTEs/PMAFs resulted from the temporal modulation of the reconnection rate during continuous reconnection. With the decay of the PMAFs associated with the FTEs, patch‐like plasma density enhancements were detected to form and propagate poleward and then dawnward. Propagation to the dawn was also suggested by the Super Dual Auroral Radar Network (SuperDARN) convection and Global Positioning System (GPS) total electron content data. We relate the temporal variation of the driving solar‐wind and magnetospheric mechanism to that of the high‐latitude and polar ionospheric responses and estimate the response time. Plain Language Summary: The solar wind‐magnetosphere coupling often occurs in a nonsteady manner. Such disturbances modify the magnetosphere‐ionosphere system. One of the most common/important processes of such nonsteady phenomena is time‐dependent dayside reconnection, as observationally evidenced by flux transfer events (FTEs), which have been, in turn, represented by ionospheric poleward‐moving auroral forms (PMAFs). Decaying PMAFs have, then, been followed by the occurrence of polar cap patches, which are regions of plasma density enhancements observed in the polar cap. This study indicates a sequence of dynamic processes from the driving solar wind, nonsteady reconnection/FTEs, PMAFs, and polar cap patches. Although a portion of this link has been studied and reported, the complete sequence of these connections and full picture of the solar wind‐magnetopause‐ionosphere coupling have rarely been reported and examined. The series of FTEs embedded in continuous reconnection and corresponding PMAFs individually occurred during persistent auroral activity strongly indicate that the FTEs and PMAFs were in response to the temporal modulation of the reconnection rate during continuous reconnection, rather than the repeated, complete turn‐on and turnoff of dayside reconnection. Our study advances the knowledge of Magnetosphere‐Ionosphere‐Coupling near the cusp region and in the open field‐line region that has been less developed than on closed field lines. Key Points: Multiple flux transfer events (FTEs) were observed to form on the dayside magnetopause under southward and duskward IMF Ground‐based observations indicate the poleward‐moving plasma streams or auroral forms (PMAFs) associated with the FTEs Development and transpolar motion of polar cap patches following the PMAFs complete the link of solar wind‐magnetosphere‐ionosphere coupling